Descriptive analysis: television uses among community in rural area, Sarawak - Alan, Ribka; Hassan, Md Salleh; Bolong, Jusang; Osman, Mohd Nizam; Lepun, Philip; Kamarudin, Shafinah (Human Resource Management Academic Research Society, 2021)
Television channel is used to convey messages of development agendas by the ruling government. Delivery of information through television channels especially in rural areas is still questionable because of the effectiveness level is influenced by their demographic features. Therefore, this study was conducted to identify the population demographics with the frequency use of television for information searching that ultimately affects the rural community quality of life. The respondents were determined based on statistical analysis. A total of 356 respondents were involved from Asap Koyan Resettlement in Belaga, Sarawak. The data collection was using questionnaires and interview as well. The results showed that the primary government information seeking via Media Prima 44.2% and RTM 39.2%, sports, and recreational information via ASTRO channel 43.9% and other information through different channels 47.6 %. The findings also show that respondents have never and rarely watched television for a week. Based on the results of this study, television has less been chosen due to the low education level and cost of living constraints. In the future, television channels advice to broadcast more programmes specifically for the Sarawak rural community at the appropriate time to watch for up grading quality of life and their development benefits.